Acupuncture for Essential Hypertension: A Meta-Analysis of Randomized Sham-Controlled Clinical Trials. (4th March 2014) - Li, Dong-Ze; Zhou, Yu; Yang, Yi-Ning; Ma, Yi-Tong; Li, Xiao-Mei; Yu, Jing; Zhao, Yan; Zhai, Hui; Lao, Lixing
Abstract : Background . Acupuncture is frequently advocated as an adjunct treatment for essential hypertension. The aim of this review was to assess its adjunct effectiveness in treating hypertension. Methods . We searched PubMed, the Cochrane Library, EMBASE, and the Chinese databases Sino-Med, CNKI, WanFang, and VIP through November, 2012, for eligible randomized controlled trials that compared acupuncture with sham acupuncture. Outcome measures were changes in diastolic (DBP) and systolic blood pressure (SBP). Results . A total of 4 randomized controlled trials were included. We found no evidence of an improvement with the fact that acupuncture relative to sham acupuncture in SBP change (n = 386 ; mean difference = −3.80 mmHg, 95% CI = −10.03–2.44 mmHg; I 2 = 99 %), and an insignificant improvement in DBP change (n = 386 ; mean difference = −2.82 mmHg, 95% CI = −5.22–(−0.43) mmHg; I 2 = 97 %). In subgroup analyses, acupuncture significantly improved both SBP and DBP in patients taking antihypertensive medications. Only minor acupuncture-related adverse events were reported. Conclusions . Our results are consistent with acupuncture significantly lowers blood pressure in patients taking antihypertensive medications. We did not find that acupuncture without antihypertensive medications significantly improves blood pressure in those hypertensive patients.